Polyvinylidene fluoride membranes impregnated at optimised content of pristine and functionalised multi-walled carbon nanotubes for improved water permeation, solute rejection and mechanical properties - Chedly Tizaoui (Separation and Purification Technology, 2015)
Pristine (CNTs-P) and oxygen-plasma-functionalised (CNTs-O) multi-walled carbon nanotubes were incorporated in polyvinylidene fluoride (PVDF) membranes using the phase inversion technique. N-methyl 2-pyrolidone solvent gave good dispersion and stability of the CNTs and hence was used for membrane fabrication. The membranes were characterised and their performances in water permeation and solutes (NOM, BrO3−, Br− and Cl−) rejection were evaluated at different CNT contents. SEM imaging of the membranes showed asymmetric finger-like porositic structure with small channelling tubes in the top layer that connect with larger channelling tubes in the deeper side. The finger-like pores were shallower in CNTs-O/PVDF membranes than the PVDF or CNTs-P/PVDF membranes. Due to oxygenated groups imparted by CNTs-O, CNTs-O/PVDF membranes were more wettable, presented higher electronegativity and hence better rejection of the anions. CNTs have increased membrane porosities and mean pore sizes and have lead to significantly enhanced water flux by up to 3.3 (CNTs-O) and 3.7 (CNTs-P) times that of pure PVDF membranes. They have also improved the rejections of NOM, bromate, bromide, and chloride at absolute values as high as 93.4%, 21.7%, 10.5%, and 9.2% respectively for CNTs-O/PVDF membrane. CNTs have also enhanced significantly the mechanical properties of the PVDF membranes and a CNT content of 0.2 mass% was optimal.